ANALYSIS OF CRITICAL THINKING SKILLS IN SOLVING HOTS TYPE PROBLEMS REVIEWED FROM STUDENTS’ METACOGNITIVE AWARENESS - Farizah Nur Amaliyah; Noer Hidayah; Dwi Shinta Rahayu (Universitas Muhammadiyah Makassar, 2025)
Critical thinking ability is one of the essential 21st-century competencies that must be developed in students. The low level of students’ critical thinking skills in solving Higher Order Thinking Skills (HOTS) problems on the Two-Variable Linear Equation System (TVLES) material is an issue that requires further investigation. This study aims to analyze students’ critical thinking skills in solving HOTS problems based on their level of metacognitive awareness. This research employed a descriptive qualitative design involving 31 students of class VIII-A at MTs Sunan Gunung Jati. Data were collected through a metacognitive awareness questionnaire, a HOTS test, and interview guidelines. Students were categorized into high, moderate, and low levels of metacognitive awareness for data analysis. The results show that students with high and moderate metacognitive awareness met all critical thinking indicators: interpretation, analysis, evaluation, and inference, and those with low metacognitive awareness fulfilled only interpretation and analysis indicators. This study provides new insights into the relationship between metacognitive awareness and critical thinking skills in learning TVLES at the junior secondary level, an area rarely explored in previous studies. The findings have strong practical implications, suggesting that mathematics teachers should integrate metacognitive strategy training Learning models to systematically foster students’ metacognitive awareness and enhance their critical thinking skills.